More pieces of news about Francisca Burdeos Zamboráin (1810), a female soldier who impersonated a man - García-Sanz Marcotegui, Ángel (Huarte de San Juan. Geografía e Historia, 2020)
This article presents new details about Francisca Burdeos, who dressed as a man since she was a teenager. She also fought as such with weapons in her hands in the first Carlist War and behind the barricades in Madrid in July 1854. She managed to hide she was a female during the battle in Madrid, and while she was employed in different jobs before and after that battle. Taking this into consideration, it is shocking that, in general, the Spanish press accepted and even praised her behaviour.